Transcriptomic study of WSSV infection in Litopenaeus vannamei lymphoid organ via single nuclei RNA sequencing - Alexandra Florea; Nick Wade; Sarah J. Salisbury; James Furniss; Clémence Fraslin; Ambre Chapuis; Kallen Sullivan; Robert Stewart; Diego Robledo; Tim P. Bean (PLoS ONE, 2026)
Background Aquaculture is the fastest growing farmed food sector and is a key part of global food security. Crustacean aquaculture, while being one of the most profitable sectors, is threatened by pathogenic diseases such as white spot disease (WSD), which results in severe stock losses and threatens animal health and welfare. In this study, we used novel techniques to study the impact of white spot syndrome virus (WSSV), the causative agent of WSD, on Pacific whiteleg shrimp ( Litopenaeus vannamei ), and uncover additional information that may be used in creating WSSV-resistant shrimp stocks. Results We successfully developed a novel nuclei isolation protocol optimized for shrimp tissues to prepare our samples for single nuclei RNA-sequencing following a pathogen challenge comprising 32 adult whiteleg shrimp infected with WSSV either through their feed or by injection. We constructed the first penaeid shrimp lymphoid organ cell atlas to improve our understanding of the characteristics of this immune organ, constructed UMAPs and identified marker genes that define distinct cell clusters to reveal the biological functions of different cell types within this organ. Conclusion By comparing gene expression between the control and WSSV-infected samples we uncovered multiple genes of interest that have the potential to be used as targets for CRISPR gene editing for WSSV-resistance in Pacific whiteleg shrimp. These genes have the potential to be valuable assets for future gene editing studies in commercially important penaeid shrimp species.